Researching Recent Researchers - Livingston, Michael C. P. (1974)
This study describes 21 of the family practitioner researchers in the 1950-1970 period. They were from varied backgrounds, generally around age 40, and located chiefly in smaller centres. Eight were solo practitioners and the remainder worked chiefly in partnerships or small groups. While the future looks brighter, greater support is needed and we must strive strenuously to record medicine “like it is”. Some principles of effective research are described.